Peran Akreditasi Dalam Penjaminan Mutu Pendidikan Di Sekolah Dasar - Maulana Amirul Adha; Conny Benyamin; Imroatin Octaviarnis; Darmawan Thalib (Media Manajemen Pendidikan, 2019)
The Education is a basic human need that is very important. The purpose of this study are (1) to know the commitment of the holy kalam Christian primary school principals in quality assurance, (2) to prepare the accreditation of the holy kalam Christian primary school, and the implementation and follow-up of the results of the accreditation of the holy kalam christian elementary school. The method used in this research is descriptive qualitative. The findings in this study are (1) the form of commitment carried out by the principal in order to maintain quality is done in various ways including optimizing the performance of the school's internal quality assurance system team, (2) there are at least 3 aspects that are prepared in implementing school accreditation, namely aspects of facilities and infrastructure (sarpras), administration, and preparation for the implementation of visitation, and (3) follow-up to improve school quality, the results and accreditation recommendations obtained are taken into consideration by schools in the framework of making policies for improving school quality, as well as improving school facilities and infrastructure. technology-based to support education and learning activities in schools.